PEMODELAN GEOTHERMAL INFLOW PERFORMANCE RELATIONSHIP PADA SUMUR PANAS BUMI DOMINASI AIR - Gandana Putra, Grha
Geothermal Inflow Performance Relationship (GIPR) is a relationship between the flow rate and the bottom well pressure on a well or geothermal field. The well bottom pressure is obtained by modeling the wellhead pressure measured on the surface during the production test. The field examined in this study is a two phase field of water dominance. In this study, the production test cannot be carried out for a long time due to the limitations of pond facilities in accommodating brine so that measurements can only be carried out at one wellhead pressure value only. Therefore, with these limitations, it is necessary to do GIPR modeling to estimate production performance. In this research, we discuss GIPR modeling in the "GG" geothermal field located in North Sumatra. Several GIPR models have been developed and GIPR models formed using the "GG" Field production test data compared to their accuracy in estimating the "GG" Field production performance. The GIPR curve formed in this study consisted of two dimensionless parameters, namely dW / dWmax and Pwf / Psat which were plotted on a Cartesian scale. The model obtained is similar to the GIPR model that was sparked by Iglesias and Moya in 1990. The average absolute error generated from the equation model formed in the "GG" Field was 11.11%.